Appreciative approach in interaction with co-workers of teachers at x school in Surabaya - Yohanes Deni Kristianto (Jurnal Psikologi Tabularasa, 2025)
This phenomenological study examines how appreciation influences interpersonal relationships among teachers at X Senior High School in Surabaya, Indonesia. In response to increasing concerns about workplace stress, teacher conflicts, and emotional disengagement, appreciation is identified as a key factor in promoting emotional well-being and professional harmony. Data were gathered through in-depth interviews with three teachers and analyzed using thematic analysis. Five main themes emerged: (1) positive dynamics of appreciative interaction, (2) appreciation as social capital, (3) the spiritual dimension of appreciation, (4) barriers to appreciative behavior, and (5) internal and external support factors. Results indicate that appreciation—expressed through simple acts like greetings, praise, or assistance—builds trust, motivation, and collegial solidarity. Teachers view appreciation not only as professional communication but also as a spiritual practice embodying gratitude and divine love. Internal factors such as proactive attitudes, emotional resilience, and past positive experiences support appreciative behaviors, while external factors like school culture and peer support reinforce them. The study concludes that embedding appreciation within school environments improves teacher morale, reduces emotional stress, and fosters a healthier, more collaborative culture. Recommendations include implementing emotional intelligence training, leadership that models appreciation, and further research across various school settings.